111k views
3 votes
Given
g(x) = 4x2 + 6
What is g(-3)

Given g(x) = 4x2 + 6 What is g(-3)-example-1
User Derek W
by
5.8k points

2 Answers

4 votes
g(-3)=42 or g(x)=42 or 42
(Not sure how your program would write the answer)
Basically what you do is input -3 into wherever there is an x. So the equation would become 4(-3)^2+6 which equals 42
User DynamicallyCRM
by
5.3k points
3 votes

Answer:


g(-3)=42

Explanation:

Given:


g(x)=4x^2+6

Let's substitute -3 for
x


g(-3)=4(-3)^2+6

Now, let's solve


g(-3)=4(9)+6


g(-3)=36+6


g(-3)=42

Hope this helps

User PTN
by
5.4k points